2013
DOI: 10.1038/ncb2842
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic framework of spindle assembly checkpoint signalling

Abstract: The mitotic spindle assembly checkpoint (SAC) delays anaphase onset until all chromosomes have attached to both spindle poles 1,2 . Here, we investigated SAC signaling kinetics in response to acute detachment of individual chromosomes using laser microsurgery. Most detached chromosomes delayed anaphase until they had realigned to the metaphase plate. A substantial fraction of cells, however, entered anaphase in the presence of unaligned chromosomes. We identify two mechanisms by which cells can bypass the SAC:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
173
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(194 citation statements)
references
References 37 publications
17
173
1
Order By: Relevance
“…Thus, miR-28-5p-mediated regulation of Mad2 may normally be dedicated to fine-tune Mad2 levels to balance against stressinduced numerical chromosomal instability. This interpretation is in line with recent findings that amounts of checkpoint proteins dictate the strength of the mitotic checkpoint (35)(36)(37). Accordingly, miR-28-5p may be part of a mechanisms that provides robustness to the process of mitosis assuring errorfree chromosome segregation.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, miR-28-5p-mediated regulation of Mad2 may normally be dedicated to fine-tune Mad2 levels to balance against stressinduced numerical chromosomal instability. This interpretation is in line with recent findings that amounts of checkpoint proteins dictate the strength of the mitotic checkpoint (35)(36)(37). Accordingly, miR-28-5p may be part of a mechanisms that provides robustness to the process of mitosis assuring errorfree chromosome segregation.…”
Section: Discussionsupporting
confidence: 78%
“…Cell lines stably expressing luciferase (Luc) and green fluorescent protein (GFP) were generated using retroviral transduction of pLPNIG (Demajo et al, 2014) followed by drug selection (100 mg/ml geneticin). For single-cell live-cell microscopy experiments, HeLa "Kyoto" cells stably expressing H2B-mCherry were used (Neumann et al, 2006;Dick and Gerlich, 2013) and were grown in Dulbecco's modified Eagle's medium (10% fetal bovine serum and 1% penicillin-streptomycin) without phenol red and riboflavin to reduce autofluorescence. Volasertib was added 1 hour prior to time-lapse recordings.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that the length of mitotic arrest and presumably the strength of the spindle checkpoint can be tuned by the number of unattached kinetochores or the severity of spindle damage (41)(42)(43). We wondered whether the Phe and D boxes of BubR1 were required for the less robust mitotic arrest triggered by low concentrations of taxol (Fig.…”
Section: The Phe and D Boxes Of Bubr1 Are Dispensable For The Spindlementioning
confidence: 99%